Li2O-ZrO2-SiO2/Al2O3 nanostructured composites for microelectronics applications. Issue 2 (February 2019) - Arcaro, S.; Wermuth, T.B.; Zampiva, R.Y.S.; Venturini, J.; ten Caten, C.S.; Bergmann, C.P.; Alves, A.K.; de Oliveira, A.P. Novaes; Moreno, R.
Abstract: Nanostructured composites of the LZS (19.58Li2 O.11.10ZrO2 .69.32SiO2 ) and LZS (19.58Li2 O.11.10ZrO2 .69.32SiO2 ) + (1, 2.5, 5 vol.%) Al2 O3 systems were obtained through a colloidal approach using nanoparticulate oxides as precursors. Stable suspensions containing 40 vol.% of solids were obtained, after deagglomeration for 24 h in a ball mill with 4% ammonium polyacrylate as a deflocculant and 15% of polymethylmethacrylate as a binder to achieve green tapes with high uniformity, easy handling and without macroscopic defects. The fired tapes displayed relative densities between 69 and 81% of their theoretical values and very low dielectric constants and loss tangents, which would allow the application of these materials in microelectronics. The addition of alumina allowed the tuning of the thermal expansion coefficients of the produced tapes, which in turn enabled the co-firing of the materials with a silicon wafer. The interfacial region between the materials is pristine and free of cracks, thus highlighting the versatility of the utilized approach towards producing fine-tuned dielectrics for advanced microelectronics applications.